Environmental Dispute Resolution Through Class Action Lawsuit - Tjukup, K.; Potra, P.R. A.; Martana, P.A.H. (Journal of A Sustainable Global South, 2020)
The procedural  law  of Class Action  is  a legal  concept  known  in  the Anglo-Saxon  legal  system  (Common  Law). Whilst  this  concept  is  not  recognised   in  the  Continental  European  legal  system  (Civil  Law),  likewise  in  Indonesian  civil procedure  that based on Herzien Inlandsch Reglement (H.I.R) and Rechtsreglement  voor de Buitengewesten  (RBg). Initially, the procedural  law of class action in Indonesian  legal  system was arranged consecutively under Law No. 23 of 1997  (Environmental Protection  Law), Law No.  8  of  1999  on Consumer Protection  and Law No. 41 of  1999  on Forestry.  The arrangement  of class action lawsuit  in the substantive  law was inspired by the recognition  of class action lawsuit  in the United  States through Article 23 of the US Federal  Rule of Civil Procedure  prescribing  that the requirements  for filing class action  lawsuit are as follows: numerosity,  commonality, typicality,  and adequacy of representation.  In Indonesia there is no procedural  law setting out the class action  lawsuit,  thus  Supreme  Court  Regulation   No.   1      of  2002  was  enacted.  The  replacement   of Law  No.  23  of  1997 (Environmental  Protection Law) by Law No. 32 of 2009 (Environmental  Protection and Management Law) allows the application of the class action with reference to this Supreme Court Regulation.  The arrangement of class action lawsuit in the Supreme Court Regulation No.  1    of 2002 still  encounters many challenges in its application.  The initial process i.e. certification  is very decisive whether the lawsuit  can be accepted  or is  qualified  as a class action lawsuit. In conjunction with this, the judges'  active role is very  important  whilst  waiting  for a specific  and adequate  legislation  to establish  the class action  procedure.  Meanwhilst,  the judges  are supposed to patch up the Supreme Court Regulation No. 1   of 2002.   K e yw o r d s :   Environmental Disputes, Procedural Law,  Class Action Lawsuit